DYNAMICS OF WALL HEATED MULTITUBULAR CATALYTIC PACKED BED REACTOR - ELGHAFOOR HASSAN, REEM HASSAN ABD (2014)
Many vapor-phase exothermic chemical reactions are carried out in small diameter packed reactors in shell and packed tube heat exchanger configuration. Design of such units requires information on kinetics and transfer coefficients to facilitate scale up. Design of control strategy for safe operation and quality control is achieved by inputoutput analysis of the actual plant operation under dynamic operating conditions. Experimental investigations on a pilot plant scale wall heated multi-tubular priV:p<l tip.il iPMilnr HynamJ4?s using knprnpyl nlrnhnl tn arpfnrtp as a modpl rp.ar.tinn are reported in this thesis. Overall heat transfer coefficients under reacting conditions and reaction kinetics are established using steady state experiments. Reaction kinetics is analyzed as 1st order reaction with Arrhenius activation energy to account for the effect of temperature. Overall heat transfer coefficients with endothermic reactions are observed to be lower than the overall heat transfer coefficients in non-reacting conditions.